2017
DOI: 10.1088/1361-6595/aa8975
|View full text |Cite
|
Sign up to set email alerts
|

Plasma instabilities of a charge breeder ECRIS

Abstract: Experimental observation of plasma instabilities in a charge breeder electron cyclotron resonance ion source (CB-ECRIS) is reported. It is demonstrated that the injection of 133 Cs + or 85 Rb + ion beam into the oxygen discharge of the CB-ECRIS can trigger electron cyclotron instabilities, which restricts the parameter space available for the optimization of the charge breeding efficiency. It is concluded that the transition from stable to unstable plasma regime is caused by gradual accumulation and ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(59 reference statements)
1
12
0
Order By: Relevance
“…For example, with the LPSC charge breeder, a 50% decrease of the O 6þ beam current has been induced by a continuous injection of 1 μA of Cs þ ions [9]. Experiments have also demonstrated that, for particular magnetic configurations, the accumulation of injected Cs in the plasma can trigger kinetic instabilities which cause the charge breeding efficiency to collapse [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, with the LPSC charge breeder, a 50% decrease of the O 6þ beam current has been induced by a continuous injection of 1 μA of Cs þ ions [9]. Experiments have also demonstrated that, for particular magnetic configurations, the accumulation of injected Cs in the plasma can trigger kinetic instabilities which cause the charge breeding efficiency to collapse [10].…”
Section: Introductionmentioning
confidence: 99%
“…plasma potential inferred from the energy spread of the extracted ion beams and the ion current transient collected by the biased disk provides further evidence for the origin of increased impurity background of the extracted beams in the unstable operating regime, being especially relevant for charge breeder ECR ion sources. 9 The electron burst collected by the biased disk can be used for estimating the order of magnitude of the total electron losses, both absolute and the fraction of the confined electrons. It is assumed that the electron density in the 100-130 cm 3 volume enclosed by the ECR zone (estimated for the range of B min /B ECR of 0.75-0.80) is 10 11 -10 12 cm −3 , which translates to the total negative charge of 1.6-21 μC, i.e., on the order of 10 μC.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the CB operation in these two facilities, the LPSC continues the R&D on the PHOENIX charge breeder. In the context of beam production for physics, the reduction of the radioactive beams contamination is crucial, and is one of the main limitation for the use of ECR charge breeders, some recent work has shown that plasma instabilities may drastically increase this contamination [3]. Concerning the PHOENIX charge breeder, simulations have shown that the magnetic structure has some deficiencies that may affect the performances.…”
Section: Contextmentioning
confidence: 99%